Lost in translation? The challenge of translating the global education goal and targets into global indicators. Issue 6 (2nd November 2017) - King, Kenneth
Abstract Abstract : In this article the history of global education goal- and target-setting is traced from 1990 to 2015. After the highly inclusive process of developing the Sustainable Development Goals (SDGs) and their targets, a much more technical process has produced the global indicators. The challenge of securing the ambitious targets for education in SDG 4 and assessing them via the global indicators is reviewed with particular attention to primary and secondary education and to skills development. A good deal of the SDG aspirations for expanded rights to, and breadth of, education appears to get lost in their translation to the indicators. The complexity of the global governance architecture for the SDGs and their implementation are also analysed, with acknowledgement of the critical lens of the Global Education Monitoring Report of 2016.